Doing without codeine: why and what are the alternatives? - Benini, Franca; Barbi, Egidio (Ital J Pediatr, 2014)
Codeine is a mild opioid widely used as an analgesic in various age groups, including various pediatric settings. It is a prodrug that owes its analgesic effect almost entirely to the principal metabolite: morphine. The genetic polymorphisms can contribute to making the pharmacokinetics of codeine hard to predict and this it is particularly important in the pediatric population because infants and children have greater susceptibility to the side-effects of morphine. In recent years there have been several reports in the literature on the risks relating to the use of codeine. In August 2012, the American Food and Drugs Administration began to revise its recommendations for the safe use of codeine and in February 2013, established that codeine should not be used for postoperative pain control in children undergoing adenoidectomy and/or tonsillectomy and did restrict the use of this drug in the pediatric population. In June 2013, the European Medicine Agency opted the same decision. In July 2013, the Agenzia Italiana del Farmaco prohibit the use of medicines containing codeine for patients under 12 years old and recommended a limited use of the drug, in many other situations. Complying with these recommendations naturally means changing habits and treatment strategies well established in pediatric practice, but other drugs, tools and techniques available enable us to continue to assure an adequate pain control in pediatric patients, irrespective of their age and situation. The article proposes same alternatives of pain control drugs.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Analgesics, Opioid; Child; Codeine; Humans; Pain Measurement; Pain, Postoperative; Tonsillectomy